Surgical Management of Modern Combat-Related Pancreatic Injuries: Traditional Management and Unique Strategies. Issue 3 (1st March 2014) - Vertrees, Amy; Elster, Eric; Jindal, Rahul; Ricordi, Camillo; Shriver, Craig
ABSTRACT: Background: Management of war-related pancreatic injuries is challenging with potential for associated concomitant injuries and complications. Methods: Retrospective record review of patients treated at Walter Reed Army Medical Center sustaining pancreatic injury during the conflicts in Iraq and Afghanistan from 2003 to 2009 was carried out. Results: Pancreatic injuries occurred in 31 of 522 (7%) patients, with the average age of 28 (range 19–54). Mechanism of injury included gunshot (68%), blast injuries (23%), and blunt injuries (10%). Distal pancreatic injuries were treated with distal pancreatectomy (55%) or drainage (45%). Head of the pancreas injuries were treated with drainage (86%). Four patients with unspecified anatomic location underwent drainage only. One patient underwent emergent pancreaticoduodenectomy (Whipple procedure) followed by completion pancreatectomy and islet cell autotransplantation. Conclusion: Management of war-related pancreatic injuries varied based on the anatomic location. Head of the pancreas injuries were primarily managed with drainage. Distal injuries were treated with resection or drainage. Autologous islet cell transplantation is a feasible option.